Gender Equality in the Romanian Local Public Institutions - Sorin Dan ŞANDOR; Felicia Cornelia MACARIE; Simona Claudia CREŢA (Transylvanian Review of Administrative Sciences, 2011)
Gender equality in public institutions is a sensitive topic considering the vast efforts of European countries to overcome the problems raised by gender inequality, gender segregation and gender discrimination in the labor market. In order to measure gender equality in public institutions and to identify the most important gender related organizational issues a questionnaire was built, tested in 2010 in one public institution, and then applied at national scale to public servants (both women and men) from local public institutions. The questionnaire focuses on gender stereotypes, sexual harassment, gender discrimination (in hiring, promotion, pay and benefits, evaluation, promotion and task distribution practices in institution) and occupational mobility.